2020
DOI: 10.1007/s00202-020-01061-z
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy expert system for metal-oxide surge arrester condition monitoring

Abstract: Metal-oxide surge arresters (MOSAs) play an important role in preventing outage situations and thus in preserving the reliability of electric power system. So far, many MOSA monitoring methods have been developed. These methods propose different indicators that are more or less reliable in MOSA monitoring and diagnostics. Another important aspect of these indicators is that each one of them can be determined with a certain estimation error. None of the indicators has been proved to be supreme. Nevertheless, un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
4
0
2
Order By: Relevance
“…This approach has the potential to increase the volume of signals available during cluster-centric signal generation. Integration of newer clustering methods, such as OPTICS [ 36 ] and Hierarchical DBSCAN [ 37 ], LSTM [ 38 ], and a fuzzy logic expert system [ 39 , 40 ] could be explored to improve the versatility of the current workflow. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach has the potential to increase the volume of signals available during cluster-centric signal generation. Integration of newer clustering methods, such as OPTICS [ 36 ] and Hierarchical DBSCAN [ 37 ], LSTM [ 38 ], and a fuzzy logic expert system [ 39 , 40 ] could be explored to improve the versatility of the current workflow. …”
Section: Discussionmentioning
confidence: 99%
“…3. Integration of newer clustering methods, such as OPTICS [36] and Hierarchical DBSCAN [37], LSTM [38], and a fuzzy logic expert system [39,40] could be explored to improve the versatility of the current workflow.…”
Section: Future Recommendationsmentioning
confidence: 99%
“…Na literatura há diversas técnicas de monitoramento e diagnóstico da degradação dos para-raios de ZnO, sendo a maioria delas baseadas na medição da temperatura e extração da corrente resistiva (IEC 60099-5 2013;Lima Júnior 2014;Lira et al 2018;Dobrić & Žarković 2020). Outros estudos foram propostos a fim de desenvolver técnicas inteligentes de diagnóstico de para-raios, em que grande parte delas utilizam inteligência artificial para compor um classificador de estados, utilizando outros indicadores, tais como relações derivadas do conteúdo harmônica da corrente (Lira & Costa 2013;Khodsuz & Mirzaie 2015;Dobrić & Žarković 2020). Adicionalmente, trabalhos têm sido publicados relatando a eficácia da terceira componente harmônica da corrente para monitoramento e diagnóstico de para-raios, com foco na aplicação em campo (Shirakawa et al 1988;Lima Júnior 2014;Metwally, Eladawy & Feilat 2017;Dobrić & Žarković 2020).…”
Section: Introductionunclassified
“…Outros estudos foram propostos a fim de desenvolver técnicas inteligentes de diagnóstico de para-raios, em que grande parte delas utilizam inteligência artificial para compor um classificador de estados, utilizando outros indicadores, tais como relações derivadas do conteúdo harmônica da corrente (Lira & Costa 2013;Khodsuz & Mirzaie 2015;Dobrić & Žarković 2020). Adicionalmente, trabalhos têm sido publicados relatando a eficácia da terceira componente harmônica da corrente para monitoramento e diagnóstico de para-raios, com foco na aplicação em campo (Shirakawa et al 1988;Lima Júnior 2014;Metwally, Eladawy & Feilat 2017;Dobrić & Žarković 2020).…”
Section: Introductionunclassified
“…They showed that the caution threshold can be used to alarm about abnormalities and estimate the abnormal probability. Fuzzy expert system is also applied in MOSA monitoring procedure [18].…”
Section: Introductionmentioning
confidence: 99%